Differential regulation of the period genes in striatal regions following cocaine exposure. - Edgardo Falcon (PLoS ONE, 2013)
Several studies have suggested that disruptions in circadian rhythms contribute to the pathophysiology of multiple psychiatric diseases, including drug addiction. In fact, a number of the genes involved in the regulation of circadian rhythms are also involved in modulating the reward value for drugs of abuse, like cocaine. Thus, we wanted to determine the effects of chronic cocaine on the expression of several circadian genes in the Nucleus Accumbens (NAc) and Caudate Putamen (CP), regions of the brain known to be involved in the behavioral responses to drugs of abuse. Moreover, we wanted to explore the mechanism by which these genes are regulated following cocaine exposure. Here we find that after repeated cocaine exposure, expression of the Period (Per) genes and Neuronal PAS Domain Protein 2 (Npas2) are elevated, in a somewhat regionally selective fashion. Moreover, NPAS2 (but not CLOCK (Circadian Locomotor Output Cycles Kaput)) protein binding at Per gene promoters was enhanced following cocaine treatment. Mice lacking a functional Npas2 gene failed to exhibit any induction of Per gene expression after cocaine, suggesting that NPAS2 is necessary for this cocaine-induced regulation. Examination of Per gene and Npas2 expression over twenty-four hours identified changes in diurnal rhythmicity of these genes following chronic cocaine, which were regionally specific. Taken together, these studies point to selective disruptions in Per gene rhythmicity in striatial regions following chronic cocaine treatment, which are mediated primarily by NPAS2.